Basic & clinical pharmacology - Katzung, Bertram G.; Masters, Susan B.; Trevor, Anthony J. (McGraw-Hill Medical ; McGraw-Hill [distributor], 2009)
Looks at the essential conepts in the science of pharmacology and its application to clinical practice
"A Lange medical book."
Previous ed.: 2007
Keywords: Clinical pharmacology; Pharmacology